2016
DOI: 10.3892/ol.2016.5374
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cancerous inhibitor of protein phosphatase 2A in human triple negative breast cancer correlates with tumor survival, invasion and autophagy

Abstract: Abstract. Cancerous inhibitor of protein phosphatase 2A (CIP2A) is a recently characterized oncoprotein which is involved in the progression of several human malignancies. The present study aimed to investigate its biological function in human triple negative breast cancer (TNBC). The expression of CIP2A in TNBC cells was examined and it was observed that CIP2A was elevated in the TNBC cell line compared with poorly invasive breast cancer cells. CIP2A depletion in TNBC cell lines inhibited proliferation, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Moreover, CIP2A depletion in TNBC cell lines resulted in inhibition of proliferation and invasion, on one hand, and induction of apoptosis and autophagy on the other hand. Another study showed that increased CIP2A expression was significantly related to basal-like and HER2+ breast cancers [40].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CIP2A depletion in TNBC cell lines resulted in inhibition of proliferation and invasion, on one hand, and induction of apoptosis and autophagy on the other hand. Another study showed that increased CIP2A expression was significantly related to basal-like and HER2+ breast cancers [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including ours reported that CIP2A promoted the aggressiveness of breast cancer (23,24). Next, we examined the effect of CIP2A depletion on Atn-inhibited invasive behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Among the three inhibitors, only Akt specific inhibitor LY294002 was able to downregulate CIP2A, similar to lapatinib treatment. Although mTOR activation is correlated with CIP2A deregulation [ 40 , 41 ], mTOR inhibition via rapamycin treatment did not suppress CIP2A expression, indicating that CIP2A-induced mTOR activation observed in our study is likely a result of CIP2A-Akt interactions (Figure 4 ). Together, our results suggest that lapatinib-induced inactivation of the PI3K/Akt pathway stimulates consequential CIP2A downregulation, and Akt activity is a critical regulator of CIP2A.…”
Section: Discussionmentioning
confidence: 54%